A casa corrente do Porto. Um estudo e projecto de reabilitação. - Simão Costa de Oliveira (2013)
Porto's current reality confirms the tendency, wich we've been gradually verifying, of its population moving and concentrating in the more peripheral areas of the city. Heading the places where this abandonment is stronger are the city's historical areas, when defined by its medieval wall and main developing streets. As a consequence, there's been an exponencial degradation of the city's historical housing, the image of a constructive and typological matrix widely spread throughout the city during a period of strong urban development. As so it happens, these traditional housing models strongly show their incompatibility with the current society's living standards, so distant from the past and so reflective of the contemporary way of living. We are talking about the typological changes in regards of the social evolutions; the programmatic evolutions that reflect the functional redistribution of the living scheme; the technological innovations that provide and demand new confort conditions in the houses interiors. The social, programmatic and technological parameters that weigh in the process of choosing a person's house have changed and, as a result, the historical model must try to adapt itself to these changes. As a result, the contemporary interventions in the existing patrimony should try to reinvent and modernize it while still respecting its heritage, saving what is important and innovating where it's needed. It is essencial that we realize this situation and take measures regarding its reversion. It is fundamental to take the reins in the process of preserving, reinventing and modernizing our housing heritage before we reach the point of no return. Therefore, the theme that we will be approaching presents a growing pertinency in the current urban, social and economical reality when we realize that, in the past few decades, Portugal has been one of the european countries that has most invested in new constructions, as oppose to being one that has least invested in the rehabilitation of its historical housing heritage. This cultural and economical waste could be fought with a much broader and systematic approach, and it is in this regard that we pretend that the current study could firm itself as a strong foundation to backing this process of historical regeneration.